2009
DOI: 10.1016/j.dental.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-sensitive optical coherence tomographic imaging of artificial demineralization on exposed surfaces of tooth roots

Abstract: Background and Objectives-The purpose of this study was to assess the potential of polarization sensitive optical coherence tomography (PS-OCT) to non-destructively measure the depth and severity of artificial demineralization on exposed root surfaces and measure the degree of inhibition by topical fluoride. Although PS-OCT imaging studies have demonstrated the utility of PS-OCT for imaging carious lesions on enamel and dentin surfaces the influence of the cementum layer that is present on intact root surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 29 publications
3
59
0
2
Order By: Relevance
“…Fried et al emphasized that the contrast of lesion images captured by PS-OCT was enhanced by depolarization of the incipient light by the lesion, 6 and that high reflectivity at the tooth surface interfered with the measurement of early enamel demineralization beneath the surface. 15 It was also indicated that the unfavorable strong reflections from the tooth surface were greatly reduced in the orthogonal polarization image, enabling better resolution of the surface zone of the lesion. 16,17 While a combination of PS-OCT with SS-OCT (PS-SS-OCT) would take advantage of both systems, 7,10 conventional SS-OCT may be still more affordable since PS-SS-OCT requires a more complicated design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fried et al emphasized that the contrast of lesion images captured by PS-OCT was enhanced by depolarization of the incipient light by the lesion, 6 and that high reflectivity at the tooth surface interfered with the measurement of early enamel demineralization beneath the surface. 15 It was also indicated that the unfavorable strong reflections from the tooth surface were greatly reduced in the orthogonal polarization image, enabling better resolution of the surface zone of the lesion. 16,17 While a combination of PS-OCT with SS-OCT (PS-SS-OCT) would take advantage of both systems, 7,10 conventional SS-OCT may be still more affordable since PS-SS-OCT requires a more complicated design.…”
Section: Introductionmentioning
confidence: 99%
“…10 Nevertheless, various solutions have been addressed for each of these drawbacks and, therefore, it appears that the use of an optimized SS-OCT system as a clinical tool may be more feasible in terms of imaging resolution and speed. 8,[10][11][12] In dental literature, there have been several reports on the use of OCT, 6,7,[13][14][15] especially for polarization-sensitive OCT (PS-OCT). It was reported that the PS-OCT was able to quantify the lesion depth and mineral loss in enamel and dentin lesions with the aid of special image analysis algorithms, 6 in which the lesion depth and mineral loss were validated by transversal microradiography (TMR).…”
Section: Introductionmentioning
confidence: 99%
“…The latter has been a widely accepted method for determining mineral loss or gain in experimentally induced incipient carious lesions 17 and has been used for the comparison and validation of other newly developed caries detection techiniques. [23][24][25] Both of these methods require the tooth to be sectioned as thin as 100 ㎛, which introduces a variation in the results and prevents the longitudinal analysis or assessment of teeth by an examiner. Furthermore, the location of the original surface of a dentinal lesion may be hard to determine because air drying dentinal lesions can result in characteristic surface shrinkage.…”
Section: Comprisons With Conventional Methodologiesmentioning
confidence: 99%
“…Its ability to in vivo imaging both hard and soft tissues of dental cavity enables early detection and intervention with dental and periodontal diseases. What is more, an OCT modality, a polarization sensitive OCT (PS-OCT) is able to record not only magnitude of light backscattered from the sample, but can reveal polarization properties of tissues, that are difficult or impossible to obtain by using other diagnostic methods [134][135][136]. This includes i.e.…”
Section: Nm Ff-oct In Teeth Imagingmentioning
confidence: 99%